Identification of genetic factors influencing flavonoid biosynthesis through pooled transcriptome analysis in mungbean sprouts - Cho, Yeonghun; Kwon, Hakyung; Kim, Byeong Cheol; Shim, Donghwan; Ha, Jungmin (Frontiers in Plant Science, 2025)
IntroductionMungbean (Vigna radiata L.) is gaining increasing interest among legume crops because of its nutritional value. Various secondary metabolites that act as antioxidants and bioactive compounds are beneficial for human health. The secondary metabolite content in plants is easily influenced by environmental conditions, and this influence varies depending on the genotype.Materials and MethodsHere, we screened six genotypes with consistently high and low content of major secondary metabolites (gallic acid, chlorogenic acid, neo-chlorogenic acid, genistin, formononetin, catechin, syringic acid, and resveratrol) across environmental replicates. Transcriptome data obtained from the individual genotypes were pooled into two groups: high and low levels of secondary metabolites.Results and DiscussionOf the 200 differentially expressed genes identified using stringent criteria, 23 were annotated in the secondary metabolite pathway. By combining the results of the secondary metabolite and transcriptome data, we identified six key genes encoding four enzymes (CCoAOMT1; Caffeoyl-CoA O-methyltransferase, CYP81E1; 4'-methoxyisoflavone 2'-hydroxylase, DFR; dihydroflavonol-4-reductase, and HCT; shikimate O-hydroxycinnamoyltransferase) that commonly influence the content of secondary metabolites (catechin, chlorogenic acid, formononetin, and genistin) in mungbeans. Through regulatory network analysis, NAC042 and MYB74 transcription factors were identified. These transcription factors regulate the expression of four key genes in mungbean, CCoAOMT1(Vradi02g00000724.1), CYP81E1(Vradi09g00002897.1), DFR(Vradi07g00001336.1), and HCT(Vradi07g00000614.1) leading to high flavonoid content.ConclusionThese results provide information on the common genetic factors involved in the production of secondary metabolites, which can improve the nutritional value of mungbeans and contribute to the development of elite mungbean cultivars.